Immediate Effects of Anodal Transcranial Direct Current Stimulation on Postural Stability Using Computerized Dynamic Posturography in People With Chronic Post-stroke Hemiparesis - Liang, Jing Nong; Ubalde, Leonard; Jacklin, Jordon; Hobson, Peyton; Wright-Avila, Sara; Lee, Yun-Ju (Frontiers in Human Neuroscience, 2020)
Postural stability is commonly decreased in individuals with chronic post-stroke hemiparesis due to multi systemic deficits. Transcranial direct current stimulation (tDCS) is a non-invasive method to modulate cortical excitability, inducing neuroplastic changes to the targeted cortical areas, and has been suggested to potentially improve motor function in individuals with neurological impairments. The purpose of this double-blinded, sham-controlled study was to examine the acute effects of anodal tDCS over the lesioned motor cortex leg area with concurrent limits of stability training on postural control in individuals with chronic post-stroke hemiparesis. Ten individuals with chronic post-stroke hemiparesis received either anodal or sham tDCS stimulation over the lesioned leg region of the motor cortex, while undergoing 20 mins of postural training. The type of stimulation to receive during the first session was pseudorandomized, and the 2 sessions were separated by 14 days. Prior to and immediately following 20 minutes of tDCS, the 10m walk test, Berg Balance Scale and dynamic posturography assessments were performed. Following a single session of anodal tDCS with concurrent postural training, we observed no changes in clinical measures of balance and walking, assessed using the 10m walk test and Berg Balance Scale. For dynamic posturography assessments, participants demonstrated improvements in adaptation responses to toes-up and toes-down perturbations, regardless of the type of tDCS received. Additionally, improved performance in shifting center of gravity was observed during anodal tDCS. Taken together, these preliminary findings suggest that tDCS can potentially be used as a feasible approach to incorporate in rehabilitation of chronic post-stroke individuals with issues related to postural control and fear of falling, and that multiple sessions of tDCS stimulation may be needed to improve functional measures of postural control and walking.